JURIDICAL REVIEW OF THE WITHDRAWAL OF PARENTAL GRANTS TO THEIR CHILDREN IS REVIEWED BY THE COMPILATION OF ISLAMIC LAW (KHI) - Abdillah, Banny; Hidayat, Anwar; Dewi, Sartika (Justisi: Jurnal Ilmu Hukum, 2024)
A grant defined as a gift to the possession of goods without remuneration or an agreement by which the grantor in his lifetime freely and irrevocably, delivers something for the purposes of the grantee who accepts the surrender. The issue raised in this study is How the judge considers case number 89./Pdt.G/2019/PA. TALU and what distinguishes the withdrawal of grants according to the compilation of Islamic law (KHI) with the Civil Code. In this study, the author uses a type of qualitative research using the normative juridical approach method, the intention is to analyze the problem, carried out by reviewing legal materials. The results of the study are in decision number 89./Pdt.G/2019/PA. TALU obtained in this study is that there is a voluntary grant of land to his child and then the grant is withdrawn by the grantor, the withdrawal of the grant that has been given according to article 212 (KHI) that the grant cannot be withdrawn except for the parents' grant to their child. In the compilation of Islamic Law limits the possibility of withdrawal of grants, unless it involves parents giving grants to their children, According to the Civil Code the withdrawal of grants can be made by expressing intention to the grantee and filing demands for the return of the goods that have been granted. These two legal systems provide different bases in the context of grantmaking.